6y-2=5u-1

Simple and best practice solution for 6y-2=5u-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y-2=5u-1 equation:


Simplifying
6y + -2 = 5u + -1

Reorder the terms:
-2 + 6y = 5u + -1

Reorder the terms:
-2 + 6y = -1 + 5u

Solving
-2 + 6y = -1 + 5u

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 6y = -1 + 2 + 5u

Combine like terms: -2 + 2 = 0
0 + 6y = -1 + 2 + 5u
6y = -1 + 2 + 5u

Combine like terms: -1 + 2 = 1
6y = 1 + 5u

Divide each side by '6'.
y = 0.1666666667 + 0.8333333333u

Simplifying
y = 0.1666666667 + 0.8333333333u

See similar equations:

| 3(2x-1)-3(4-2x)=6 | | 3y/4-4=8 | | (2x-29)+(x+5)=180 | | 8v+2-3v-6= | | 0.8+0.2-5x= | | 16x+112=64+132x+14x | | 8+4(z-2)=-5x+8 | | x+0.2-5x= | | -6(x+2)+15=-4x-7 | | 3.2=4.4-0.3x | | (7x+1)+(13x+9)=90 | | 2(4-3x)-10=2x-74 | | 4x^3-9x^2-2=0 | | 13y-1.8=-5y+3.6 | | 4(5c+1)-26=17c+2 | | 33t=-46 | | X*.6=25 | | 5√6/4√50 | | 3x-8=4(x+4) | | 3m-7+m+23= | | 3x+29=6x+8 | | 4(x-3)=x-12 | | 8x%3-2x%4=-14 | | 4x-27andX+39= | | -11n-7=11 | | k/6-7=-4 | | 2(2x+5)+2x=250 | | 6x-15=5x+6-2x | | 1/2in(e^6) | | (5√6)/(4√50) | | (12n+99)+(8n+8)= | | 20n-16=0 |

Equations solver categories